Islamic Self-Regulated Learning on Gender Differences in Prospective College Lecturers - Khusnul Khotimah, Umi (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The need to understand how Islamic principles and self-regulated learning (SRL) interact, particularly in the context of the learning experiences of prospective college lecturers, as well as how gender differences in self-regulated learning practices among prospective college lecturers can be addressed. By understanding this, we can develop effective strategies and interventions to support their professional development and enhance the quality of teaching and learning in higher education institutions. This research utilizes a Systematic Literature Review (SLR). Islamic self-regulated learning (SRL) is pivotal in shaping the educational landscape, particularly concerning prospective college lecturers and their gender dynamics within Islamic frameworks. Both men and women engage in self-awareness and intention setting, aligning their educational pursuits with Islamic principles. Goal setting extends beyond academia, encompassing spiritual and moral aspirations, tailored to their respective roles in the community. While monitoring progress and adjusting strategies are inherent, gendered approaches emerge influenced by societal norms. Seeking guidance from Islamic sources is universal, yet interpretations may diverge based on gender roles and cultural contexts. Integration of Islamic values into teaching underscores their shared commitment, albeit through nuanced expressions shaped by individual experiences and perspectives.